2015
DOI: 10.3892/ol.2015.3204
|View full text |Cite
|
Sign up to set email alerts
|

Trans-bronchoscopy with implantation of 125I radioactive seeds in patients with pulmonary atelectasis induced by lung cancer

Abstract: Abstract.To evaluate the role of low-dose-rate interstitial brachytherapy using trans-bronchoscope 125 I radioactive seeds implantation in patients with pulmonary atelectasis induced by lung cancer, in terms of feasibility, safety, quality of life (QOL), and survival time. Between April 2008 and June 2011, 15 patients from two medical institutions that had obstructive pulmonary atelectasis caused by inoperable lung cancer were assigned to receive 125 I implantation endoluminal brachytherapy by bronchoscopy. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Nerve injury, defined as limb paresthesia or leg weakness, was detected in one patient, who recovered completely in 2 months without special therapy. Numerous studies had proven the safety of 125 I seed implantation brachytherapy . In this study, fewer complications were observed in the 125 I seed implantation procedure than in the MWA procedure.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Nerve injury, defined as limb paresthesia or leg weakness, was detected in one patient, who recovered completely in 2 months without special therapy. Numerous studies had proven the safety of 125 I seed implantation brachytherapy . In this study, fewer complications were observed in the 125 I seed implantation procedure than in the MWA procedure.…”
Section: Discussionmentioning
confidence: 55%
“…Achieving a complete response (CR) is important when local therapy is performed in selected patients. Iodine‐125 ( 125 I) radioactive seed implantation has been shown to be efficient in treating many types of malignant tumors , especially in complex situations . This study focused on whether 125 I seed implantation after MWA could improve local control in selected patients with rRPLs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 125 I radioactive seed implantation had proved its efficacy in various malignant tumors [10,11,12,13]. The results of Lu et al revealed that trans-bronchoscopy 125 I radioactive seed implantation brachytherapy could improve the survival and quality of life of patients with pulmonary atelectasis induced by intralumi-nal airway obstruction [14]. However, studies on the efficacy of computed tomography (CT)-guided 125 I radioactive seed implantation in patients with malignant airway compression (MAC) related to advanced lung cancer are still rare.…”
Section: Purposementioning
confidence: 99%
“…Lung tumors located adjacent to the hilus, large vessels, or heart cannot be treated via radical resection …”
Section: Implanting Modalitiesmentioning
confidence: 99%